Respuestas

  • Usuario de Brainly
2013-12-10T22:07:15+01:00
**2x + 4 = 16 
2x = 16 - 4
2x = 12
x = 6

**7x + 8 = 57
7x = 57 - 8
7x = 49
x = 7

**x + 2 = 16 - 6x
x + 6x = 16 - 2
7x = 14
x = 2

**x - 1 = 9 - x
x + x = 9 + 1
2x = 10
x = 5

**5x - 5 = 25
5x = 25 + 5
5x = 30
x = 6

**3x + 4 = 2*(x + 4)
3x + 4 = 2x + 8
3x - 2x = 8 - 4
x = 4

**5*(x - 1) - 6x = 3x - 9
5x - 5 - 6x = 3x - 9
5x - 6x - 3x = -9 + 5
-4x = -4
x = 1

**4*(x - 2) + 1 + 3x = 5*(x + 1)
4x - 8 + 1 + 3x = 5x + 5
4x + 3x - 5x = 5 + 8 - 1
2x = 12
x = 6